Carbohydrate hydrogels with stabilized phage particles for bacterial biosensing: bacterium diffusion studies - Balcão, V. M. (2014)
Bacteriophage particles have been reported as potentially useful in the development of diagnosis tools for pathogenic bacteria as they specifically recognize and lyse bacterial isolates thus confirming the presence of viable cells. One of the most representative microorganisms associated with health care services is the bacterium Pseudomonas aeruginosa, which alone is responsible for nearly 15 % of all nosocomial infections. In this context, structural and functional stabilization of phage particles within biopolymeric hydrogels, aiming at producing cheap (chromogenic) bacterial biosensing devices, has been the goal of a previous research effort. For this, a detailed knowledge of the bacterial diffusion profile into the hydrogel core, where the phage particles lie, is of utmost importance. In the present research effort, the bacterial diffusion process into the biopolymeric hydrogel core was mathematically described and the theoretical simulations duly compared with experimental results, allowing determination of the effective diffusion coefficients of P. aeruginosa in the agar and calcium alginate hydrogels tested.